What doesn’t kill you makes you fitter: A systematic review of high-intensity interval exercise for patients with cardiovascular and metabolic diseases - Levinger, I.; Shaw, C.; Stepto, N.; Cassar, S.; McAinch, A.; Cheetham, C.; Maiorana, Andrew (Libertas Academica Ltd., 2015)
High-intensity interval exercise (HIIE) has gained popularity in recent years for patients with cardiovascular and metabolic diseases. Despite potential benefits, concerns remain about the safety of the acute response (during and/or within 24 hours postexercise) to a single session of HIIE for these cohorts. Therefore, the aim of this study was to perform a systematic review to evaluate the safety of acute HIIE for people with cardiometabolic diseases. Electronic databases were searched for studies published prior to January 2015, which reported the acute responses of patients with cardiometabolic diseases to HIIE (≥80% peak power output or ≥85% peak aerobic power, VO2peak). Eleven studies met the inclusion criteria (n = 156; clinically stable, aged 27–66 years), with 13 adverse responses reported (~8% of individuals). The rate of adverse responses is somewhat higher compared to the previously reported risk during moderate-intensity exercise. Caution must be taken when prescribing HIIE to patients with cardiometabolic disease. Patients who wish to perform HIIE should be clinically stable, have had recent exposure to at least regular moderate-intensity exercise, and have appropriate supervision and monitoring during and after the exercise session.